2017
DOI: 10.1111/1556-4029.13502
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of Modern Arrowhead Tips on Human Skin Analog

Abstract: Archery has experienced a recent resurgence in participation and has seen increases in archery range attendance and in children and young adults seeking archery lessons. Popular literature and movies prominently feature protagonists well versed in this form of weaponry. Periodic homicide cases in the United States involving bows are reported, and despite this and the current interest in the field, there are no manuscripts published on a large series of arrow wounds. This experiment utilizes a broad selection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…In addition, an arrow can tangentially hit its target, resulting in a linear slit that resembles a laceration. It is interesting to note that these same findings were discovered by Sung et al while discussing the forensic pathology of arrow wounds in the 21st century [ 5 ].…”
Section: Reviewsupporting
confidence: 69%
See 1 more Smart Citation
“…In addition, an arrow can tangentially hit its target, resulting in a linear slit that resembles a laceration. It is interesting to note that these same findings were discovered by Sung et al while discussing the forensic pathology of arrow wounds in the 21st century [ 5 ].…”
Section: Reviewsupporting
confidence: 69%
“…In addition, a recent poll by Responsive Management for the Archery Trade Association conducted in 2014 revealed an increase in the participation in archery recreational events amongst United States (US) adults [ 4 ]. A more recent experiment conducted by forensic pathologists demonstrated how modern arrowheads can mimic both stab and gunshot wounds [ 5 ]. This experiment also noted that studies on arrow injuries were limited, and while they supplied a detailed report for classification of morphologic variations, they failed to mention management or treatment options for an arrow wound [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Muzzy Phantom penetrated the blubber layer resulting in a distinct X‐shaped impression 2 cm long and 2 cm wide, making it the closest match in size and shape to the X‐shaped lesions on Cases 1 and 2 (Figure i). While the skin on lesions in Case 1 and Case 2 were markedly more agape than the thin incised lesions made by hand on the test carcasses, gaped wounds have been documented in broadhead arrow injuries due to decomposition and healing (Bradley‐Siemens, Brower, & Kagan, ) or entry direction (Sung et al, ).…”
mentioning
confidence: 93%
“…Objects with potential to leave X‐shaped impact patterns in soft tissue include spearfishing tips and broadhead hunting arrows (Byard et al, ; DiMaio & DiMaio, ). Fishing spears and harpoons are equipped with a single edged blade, leaving a singular, oval penetrating wound on associated animals and was ruled out as the source of the lesions (Byard et al, ; Sung, Kesha, Hudson, Root, & Hlavaty, ). When comparing lesions to documented forensic case studies, we found that in human and animal cases, four‐ to five‐point broadhead arrows were identified as the weapon responsible for causing X‐shaped lesions (DiMaio & DiMaio, ) and broadhead arrow wound patterns mimic the number and arrangement of blades on the arrow tip (1–6 blades; Smith‐Blackmore & Robinson, ; Sung et al, ).…”
mentioning
confidence: 99%
See 1 more Smart Citation